Hubungan Status Pekerjaan Orang Tua Dengan Hasil Belajar Siswa - hastiana, yetty; saputri, wulandari; septia, bellah (Florea : Jurnal Biologi dan Pembelajarannya, 2023)
The purpose of this study is to see how the relationship between parents' work and student learning outcomes. The methods in this research include descriptive research methods. The data analysis technique of this study is the Miles and Huberman model which consists of data reduction, data presentation, and conclusion and verification. The results of this study show that parents in class VII.6 and VII.7 SMP Muhammadiyah work mostly as entrepreneurs, 34% and at least 9% as formal private companies. Meanwhile, the results of the daily tests from Muhammadiyah Middle School students have achieved KKM scores in science subjects, in class VII.6 there were 18 people (82%) and VII.7 there were 21 people (95%) for the 2021/2022 Academic Year. Based on this, it can be concluded that there is no work relationship with student learning outcomes because when parents are busy with their work, children are still able to improve good and high learning outcomes. This shows that one of the factors that increases student learning outcomes is not only parents' employment status but there are other factors such as internal and external factors. External factors, for example, come from family, school, community, for example, parents' education, parents' work and parents' income. Meanwhile, internal, namely factors that come from within the individual student both physically and spiritually, such as self-motivation